APOC3 induces endothelial dysfunction through TNF-α and JAM-1. Issue 1 (December 2016) - Tao, Yun; Xiong, Yisong; Wang, Huimin; Chu, Shaopeng; Zhong, Renqian; Wang, Jianxin; Wang, Guihua; Ren, Xiumei; Yu, Juan
Abstract Background The fatality rate for cardiovascular disease (CVD) has increased in recent years and higher levels of triglyceride have been shown to be an independent risk factor for atherosclerotic CVD. Dysfunction of endothelial cells (ECs) is also a key factor of CVD. APOC3 is an important molecule in lipid metabolism that is closely associated with hyperlipidemia and an increased risk of developing CVD. But the direct effects of APOC3 on ECs were still unknown. This study was aimed at determining the effects of APOC3 on inflammation, chemotaxis and exudation in ECs. Methods ELISA, qRT-PCR, immunofluorescence, flow cytometry and transwell assays were used to investigate the effects of APOC3 on human umbilical vein endothelial cells (HUVECs). SiRNA-induced TNF-α and JAM-1 silencing were used to observe how APOC3 influenced the inflammatory process in the ECs. Results Our results showed that APOC3 was closely associated with the inflammatory process in ECs, and that this process was characterized by the increased expression of TNF-α. Inflammatory processes further disrupted the tight junctions (TJs) between HUVECs by causing increased expression of JAM-1. JAM-1 was involved in maintaining the integrity of TJs, and it promoted the assembly of platelets and the exudation of leukocytes. Changes in its expression promoted chemotaxis and the exudation of ECs, which contributed to atherosclerosis. While the integrity of the TJs was disrupted, the adhesion of THP-1 cells to HUVECs was also increased by APOC3. Conclusions In this study, we describe the mechanism by which APOC3 causes inflammation, chemotaxis and the exudation of ECs, and we suggest that controlling the inflammatory reactions that are caused by APOC3 may be a new method to treat CVD.